Legal marijuana : perspectives on public benefits, risks and policy approaches - Gonzalez, Joaquin Jay, III; McGee, Mickey P., 1949- (McFarland & Company, Inc., 2018)
"The legalization of marijuana has spread rapidly throughout the U.S., from just a handful of states ten years ago to now more than half, as well as the nation's capital. This collection of essays explains the benefits and concerns, the policies and actions, and the future of this controversial issue"--